Social practices of nurse care coordination using sensor technologies - Challenges with an alert system adoption in assisted living communities for older adults - Isa Jahnke; Nathan Riedel; Mihail Popescu; Marjorie Skubic; Marilyn Rantz (Elsevier, 2021)
Objectives: From the view of everyday practices and the socio-technical coordination lens, this study aimed to analyz the gap between creators' intention and the users' implementation (mainly nursing staff and social workers) of an alert system in assisted living communities. Methods: Qualitative methods were employed by way of five user interviews and focus groups with six system developers. Modeling instruments were applied for data collection to analyze the different clinical workflows versus the expectations of the system development team. Results: Results indicate that the clinical workflow changed over time, which led to a mismatch of nurse care coordination, social practices, and technology use. The results show different mental models of the socio-technical practice. Applying the coordination theory, the following recommendations could be developed to overcome the mismatch. First, it is recommended that nursing staff set goals together. Second, a communication rhythm with the nursing staff and developer teams should be established, with guided questions to facilitate the conversation, to shed light on the different workflows and the difference in social practices when using sensor technologies or alert systems. Third, a checklist for new employees should be created so they know how and on which devices to use the alert system. Fourth, the user experience with the alert system should be improved (e.g., an improved user interface). Conclusions: This work indicates recommendations to close the mental model gap to overcome the mismatch between optimal use of the alert system and how the nursing staff is actually using it.